Cyclopentane Hydrate for Hydrate Wetting Studies - Abdulkader, Bashir Mohammed Hissen (The University of Bergen, 2013)
Abstract Gas hydrates are often found in the systems for production of petroleum, natural gas and water systems, which is highly undesirable. In some systems the hydrates can form rapidly into large plugs and agglomerate in the transportation lines and blockage the systems, especially, in the deep sea and permafrost regions. Generally, hydrates plug agglomeration has been prevented using one of three methods, including anti-agglomeration in which surfactants are used as anti-agglomeratants. In this thesis, experiments have been conducted to observe the behavior of cyclopentane hydrates and provide data on the morphology, kinetics and the determination of hydration numbers. Cyclopentane hydrate systems have been investigated to determine the effects of three additives used for enhancing the kinetic rate using two types of surfactants (5×10-3M span20 and 5×10-4M tween20) and an organic compound (4 wt% tetrahydrofuran; THF) in two different ratios of water to hydrate former in order to achieve a broad experimental data set for systematic evaluation. In this systems, we have is used 3.5 wt% of saline water. The results show that the morphology of cyclopentane hydrates during the formation depends on the type of the surfactants, while the tetrahydrofuran does not have a visual effect on the hydrate morphology. The determined hydration numbers are a function of the emulsion type (formed by the surfactants) and the contribution of the tetrahydrofuran in the hydrate cavities as a guest molecule. Water in oil emulsion causes higher hydration number, while oil in water emulsion causes lower one. The formation time measurements of cyclopentane hydrates show that the addition of THF into the cyclopentane hydrate system in presence or absent of surfactants, promotes the hydrate formation. The addition of surfactants affected the hydrate formation according to the emulsion type, in which tween20, which forms an oil in water emulsion has faster formation rate than span20, which forms a water in oil emulsion. MAMN-KJEM ...